DGI-072 The Use of Linezolid in Neurosurgery: The Example of a French Teaching Hospital. (12th March 2013) - Raynaud, S; Merienne, C; Toft, J; Tiravy, JJ; Civade, E
Abstract : Background: Linezolid (LNZ) is an antibiotic indicated for the treatment of methicillin-resistant Gram-positive infections. Following recent unavailability of fosfomycin in France, local standards for the treatment of nosocomial meningitis and nosocomial brain abscesses (NM-NBA) have temporarily changed. Indeed, in Toulouse's Teaching Hospital, the Anti-infectious Committee has decided to modify its recommendations, changing fosfomycin to LNZ. At the same time, the use of LNZ is strictly controlled in our hospital, in order to preserve antimicrobial activity as long as possible. Purpose: To present an overview of the use of LNZ in a neurosurgery ward, in Toulouse's teaching hospital. Materials and Methods: We analysed the prescriptions for LNZ between 1 January 2011 and 1 August 2012, collecting data on: type of infection, germ and antibiotic sensitivity, treatment duration, total cost of antibiotic treatment. Results: When fosfomycin was still available, LNZ was only prescribed to six patients, none of whom was treated for NM-NBA. When fosfomycin became unavailable, 72 prescriptions were written for LNZ, of which 59 (82%) were for NM-NBA. Of these 59 prescriptions, 54 (92%) were initially empirical; 45 (76%) were revaluated at day 3 with advice from a senior infectious disease specialist, which resulted in 19 treatment discontinuations (42%). Moreover, 29% (17/59) of identified germs were multi-resistant and in 44% of cases (26/59) no germ was isolated. In one case, the isolated germ was resistant to LNZ. The substitution for fosfomycin by LNZ has led to an estimated extra cost of 2014 euros per month. Conclusions: Unavailability of fosfomycin has led to a strong increase in the use of LNZ, particularly for the treatment of NM-NBA, causing extra costs and increasing the risk of LNZ resistance. Careful use of this antibiotic, with the contribution of Hospital Pharmacists, should help us preserve its potential. No conflict of interest.